Adapting and updating the concepts related to the field of foreign language teaching - BOUHECHICHE, Arezki (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
This article aims to highlight the terminology inherent in the teaching of foreign languages in order to help researchers and other specialists to standardize and homogenize its use. Therefore, this paper demonstrates that the choice of the concepts depends fundamentally on the evolution of the discipline. Hence, it is essential to adapt and update those concepts in order to succeed in the epistemological, theoretical and technical axes of any researchin foreign language teaching.